Investigation of microstructure and dielectric behavior of Bi2/3Cu3-xMgxTi4O12(x=0, 0.05, 0.1 and 0.2) ceramics - Rai V.S.; Pandey S.; Verma M.K.; Kumar V.; Prajapati D.; Mandal K.D. (My University, 2025)
In this manuscript, We have reported the synthesis and characterization of Mg-doped and un-doped BCTO ceramic (Bi2/3Cu3-xMgxTi4O12, x=0, 0.05, 0.1 and 0.2) sintered at 1173 K for 8 h, which have been prepared by the semi-wet route. The Single-phase formation of ceramic was approved by the XRD pattern. The Microstructural properties were studied by TEM. The samples were characterized by dielectric and impedance spectroscopic properties. The dielectric constant (r) was calculated to be 3024 for BCTO ceramics at 423 K and 100Hz. The tangent loss (tan δ) value was calculated to be 0.45 for BCTO ceramic at 423 K and 10 kHz. The internal Barrier Layer Capacitance (IBLC) mechanism was responsible for the high value of the dielectric constant. It was observed from Impedance studies that there was the existence of the Maxwell-Wagner form of relaxation in the ceramics. In the temperature range 300-500 K, the Bi2/3Cu3-xMgxTi4O12 (where x=0, 0.05, 0.1, 0.2) ceramic follows Arrhenius behavior with an almost single slope. Pervoskite material plays a significant role in the biosensing field like DNA hybridization. This research provided a newtype and promising perovskite for the development of efficient biosensors. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.